EVALUATION OF CORRUPTION PREVALENCE IN THE CONTEXT OF THE DEVELOPMENT OF THE LATVIAN ECONOMY - Vilks, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper analyses some trends in the development of the Latvian economy and the evaluation of the prevalence of corruption, based on the results of different international studies. The initial situation analysis in the field of the economy does not indicate any direct negative correlations as to the scope of economic and financial corruption. Major essential studies on corruption admit that corruption is related to an ineffective, non-transparent public administration system, it facilitates irrational use of public resources, increases the uncontrollable economic segment, decreases the population welfare level, undermines confidence in public institutions, etc. Prevention and combating of corruption, despite the strivings of law enforcement authorities, are considered to be insufficiently effective. In the studies practically no attention is paid to the possible positive elements of corruption, which are hard to be identified. In the paper the author also outlines unconventional aspects of corruption.